Estratégias para viabilizar e fomentar a produção de habitação popular inclusiva no município de Curitiba - Torquato, Mario Leonardo (2017)
The Brazilian housing policy adopted, since the early 60’s, a model that produces large housing complex in distant and segregated areas of the cities. While the popular housing offer is assured, low-income families are deprived from the benefits and opportunities of the city, bringing to light the social and spatial segregation that characterizes many Brazilian large cities. Considering that local housing policies may be the answer to change this model, this paper aims to propose strategies to assure financial feasibility to inclusionary housing at Curitiba city, capital of Parana State and the most populous city of south Brazil. The basic hypothesis of the proposal is that, through the adaptation of land use and occupation parameters, it would be feasible to demand from a real estate developer the supply of housing units at lower prices than those practiced by the market at urban complex inserted areas. The inclusionary housing units would be designated to families with incomes from three until nine “salários mínimos” At first the paper approaches the history of Brazilian housing policies, the social and spatial segregation of Brazilian cities and discusses about everyone’s right to access and benefit from the city. After that, strategies to make feasible and enhance the inclusionary housing production in Curitiba city will be developed. Financial simulations proved that the hypothesis was feasible at two demarcated areas from the developer’s perspective.